Perilaku Merokok Dan Pengaruhnya Terhadap Prestasi Belajar PAI Siswa SMA di Bandung Selatan - Dwi Fikry Al-Ghifary; Firmansyah (Gunung Djati Conference Series, 2022)
The purpose of this research is to determine the effect of smoking behavior on the learning achievement of high school students in South Bandung. This research uses descriptive method with cross-sectional type. Respondents in this study amounted to 52 high school students in South Bandung. the researchers made men as the main respondents aged 15-19 years who were high school/vocational or MA students. The highest age is 17 years old or 55.77%, 34 people or 65.38% high school students have the status, with the average most students getting above the KKM as many as 39 people or 75% and the intensity of smoking 1-4 cigarettes per day is 31 or 59.62%. The effect of smoking behavior on learning achievement is negative, where the achievement value is -0.125, meaning that if learning achievement is increased by 1 unit, smoking behavior will decrease by 0.125. Based on the results of the study, it can be concluded that the regression analysis of respondents based on the majority of students, amounting to 52 people, can be concluded that the influence of smoking behavior on high school students in South Bandung is mostly light smokers so that the effect of smoking behavior on student achievement is not very significant.